Experiences of historical introductions in Majorca: the case of "Ranunculus weyleri" (Ranunculaceae) - Cursach, Joana; Orell, Jeroni J.; Rita, Juan (Mediterranean Botany, 2018)
Conservation translocations did not begin to be documented until the late decades of the twentieth century in Spain. However, there is evidence that some endemic species were translocated in 1958 in Majorca (Balearic Islands) because the blasting of the highest mountain peak on the island for the installation of an American radar station could have endangered the survival of these endemic species. This is the case for Ranunculus weyleri Marès ex Willk., a threatened plant that consists of a few subpopulations with disjoint distribution. The aim of this study was (i) to search the personal documents of the botanist Jeroni Orell Casasnovas (1924-1995) —delegate of the Societat d’Història Natural de les Balears for the protection of the Puig Major flora before the blasting in 1958— to obtain information about this introduction and (ii) to perform a demographic census of its current conservation status. After the introduction in 1958, monitoring of the translocated plants in the following years 1963 and 1964 confirmed that the establishment was successful; currently, this subpopulation consists of 63 adult plants. Overall, the conservation translocation of R. weyleri sixty years ago was successful. Finally, we underline the utility of field notebook data for historical botanists who gathered valuable information but did not publish it elsewhere and the importance of publishing the results of current translocation actions, whether they succeed or not.